Harvest and post-harvest handling practices associated with Fumonisin B1 Contamination in maize (Zea mays L.): dietary exposure and risk characterization in Eastern Ethiopia - Mohammed, Abdi; Seid, Awol; Terefe, Habtamu; Cervini, Carla; Verheecke-Vaessen, Carol (Springer, 2022)
Maize is the main staple food crop in the eastern part of Ethiopia. However, maize loss is a major issue due to fungal contamination especially at the post-harvest stage owing to inadequate handling practices. This study aimed to assess post-harvest handling and awareness against fungal development and fumonisin B1 (FB1) in maize and to calculate risk exposures of FB1. A total of 197 maize samples (grain and flour) were collected from five districts (Haramaya, Kersa, Meta, Oda Bultum, and Tullo). FB1 was detected using LC–MS/MS qTRAP. Exposure assessment was done based on the maize consumption rate per day in Ethiopia for different age groups (infants, children, and adults). Risk characterization depends on the margin of exposure (MoE) combined with the lower confidence limit of the benchmark dose level (BMDL). About 81% of farmers were not physically separating undamaged maize ears with damaged from either birds or fungi. Moreover, 100% were not using improved storage material. In storage samples, FB1 was detected as high as 1058 μg/kg ± 234 in the Kersa district while a minimum of 22.60 μg/kg ± 5.27 in Meta. In flour samples, the maximum FB1 (327 μg/kg) was detected from the Oda Bultum district. The maximum exposure of infants was estimated at Kersa (1131 µg/kg bw/day), followed by Oda Bultum (1073 µg/kg bw/day) and Haramaya (854 µg/kg bw/day). Overall, FB1 exposures ranged from 6.09 to 1131 µg/kg bw/day, which is 3 to 500 µg/kg bw/day higher than the maximum tolerable daily intake of 2 µg/kg bw/day recommended by the World Health Organization. The MoE ranged from 0.15 to 176, with infants being at higher risk than adults. The study highlights the urgent need to enhance growers’ awareness and knowledge of good post-harvest practices to reduce mycotoxin contamination in maize. Further biomarker analysis must be pursued to determine the risk exposure assessment for different age groups in these areas with a priority for the Kersa district.
Keywords: Awareness assessment; Exposure assessment; Fumonisin contamination; Maize; Post-harvest handling; Ethiopia